Cryopreservable arrays of paper-based 3D tumor models for high throughput drug screening. Issue 5 (22nd February 2021) - Samara, Bisan; Deliorman, Muhammedin; Sukumar, Pavithra; Qasaimeh, Mohammad A.
Abstract : Schematic representation of the methodology developed for creating cryopreservable high throughput paper-based arrays of 3D tumor models for drug screening applications. Abstract : Three-dimensional (3D) tumor models have gained increased attention in life-science applications as they better represent physiological conditions of in vivo tumor microenvironments, and thus, possess big potential for guiding drug screening studies. Although various techniques proved effective in growing cancer cells in 3D, their procedures are typically complex, time consuming, and expensive. Here, we present a versatile, robust, and cost-effective method that utilizes a paper platform to create cryopreservable high throughput arrays of 3D tumor models. In the approach, we use custom 3D printed masks along with simple chemistry modifications to engineer highly localized hydrophilic 'virtual microwells', or microspots, on paper for 3D cell aggregation, surrounded by hydrophobic barriers that prevent inter-microspot mixing. The method supports the formation and cryopreservation of 3D tumor arrays for extended periods of storage time. Using MCF-7 and MDA-MB-231 breast cancer cell lines, we show that the cryopreservable arrays of paper-based 3D models are effective in studying tumor response to cisplatin drug treatment, while replicating key characteristics of the in vivo tumors that are absent in conventional 2D cultures. This technology offers a low cost, easy, and fast experimental procedure, and allows for 3D tumor arrays to be cryopreserved and thawed for on-demand use. This could potentially provide unparalleled advantages to the fields of tissue engineering and personalized medicine.